Phyllactinia himalayensis, a new species on Juglans regia from Pakistan - Zafar, Irsa; Afshan, Najam-Ul-Sehar; Khalid, Abdul Nasir; Liu, Shu-Yan; Tang, Shu-Rong (Phytotaxa, 2022)
A powdery mildew fungus of the genus Phyllactinia was found on leaves of Juglans regia in Pakistan. This species is well characterized by having large-sized chasmothecia, rather short appendages and small ascospores. Sequences retrieved from this species formed a separate clade distant from the clade constituted by Phyllactinia juglandis, a common species on different hosts of the Juglandaceae in Asia. On account of biological and morphological differences from phylogenetically related species, the new species is described and illustrated as Phyllactinia himalayensis sp. nov.